2020
DOI: 10.7150/jca.44754
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of METTL3 associated with the metabolic status on 18F-FDG PET/CT in patients with Esophageal Carcinoma

Abstract: Background: To investigate the expression of methyltransferase 3 (METTL3) and its relationship with 18 F-FDG uptake in patients with esophageal carcinoma (ESCA). Materials and methods:This study analyzed the expression of METTL3 in ESCA and its relationship with clinicopathological features by The Cancer Genome Atlas (TCGA) database. Immunohistochemical staining was performed on 57 tumor tissues of ESCA patients who underwent PET/CT scan before surgery to evaluate the expression of METTL3, glucose transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…Finally, we verified the differential expression of NPM1 in LUAD and normal samples by qRT-PCR and IHC staining. The specific procedures refer to previous studies (14), and see the Supplementary Materials for details.…”
Section: Expression Of Npm1 In Luadmentioning
confidence: 99%
“…Finally, we verified the differential expression of NPM1 in LUAD and normal samples by qRT-PCR and IHC staining. The specific procedures refer to previous studies (14), and see the Supplementary Materials for details.…”
Section: Expression Of Npm1 In Luadmentioning
confidence: 99%
“…Consistently, it has been recently reported that METTL3 expression was related to TNM stage in patients with nasopharyngeal carcinoma, 8 as well as tumor size in patients with esophageal carcinoma. 17 Liu et al. 18 have clarified that high METTL3 expression was associated with poor prognosis of patients with oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, studies have shown that GLUT1 is highly expressed in oral (4), gastric (5), breast (6), colorectal (7), and ovarian cancers (8). In previous studies (9), we found that GLUT1 was highly expressed in ESCA and strongly correlated with metabolic parameters of 18 F-FDG PET/CT imaging, but we failed to carry out more studies on the biological function of GLUT1 in ESCA.…”
Section: Introductionmentioning
confidence: 86%
“…Clinical samples were obtained from 50 patients with ESCA who were surgically treated at Taihe Hospital Affiliated of Hubei University of Medicine from February 2016 to September 2017. The content of GLUT1 was detected by IHC according to the method previously described (9). The ESCA tissue and the paracarcinoma tissues were prepared into 3 mm paraffin sections and incubated with mouse monoclonal antibodies of GLUT1 (1:200, Abcam, USA) at 4°C overnight in a refrigerator.…”
Section: Immunohistochemistrymentioning
confidence: 99%